Immununochemical Markers of the Amyloid Cascade in the Hippocampus in Motor Neuron Diseases - Gómez-Pinedo, Ulises; Villar-Quiles, Rocio N.; Galán, Lucia; Matías-Guiu, Jordi A.; Benito-Martin, Maria S.; Guerrero-Sola, Antonio; Moreno-Ramos, Teresa; Matías-Guiu, Jorge (Frontiers in Neurology, 2016)
Background: Several findings suggest that the amyloid precursor protein (APP) and the amyloid cascade may play a role in motor neuron disease (MND). Objective: Considering that dementia is one of the most frequently non-motor symptoms in ALS and that hippocampus is one of the brain areas with greater presence of amyloid related changes in neurodegenerative diseases, our aim was to analyse the molecular markers of the amyloid cascade of APP in pathology studies of the hippocampus of autopsied patients with ALS and ALS-FTD. Methods: We included 9 patients with MND and 4 controls. Immunohistochemical studies and confocal microscopy were used to analyse the expression of APP, TDP-43, pho-TDP-43, Aβ, AICD peptide, Fe65 protein, and pho-TAU in the hippocampus of 7 patients with ALS, 2 patients with ALS-FTD, and 4 controls. These findings were correlated with clinical data. Results: Patients displayed increased expression of APP and Aβ peptide. The latter was correlated with cytoplasmic pho-TDP-43 expression. We also found decreased Fe65 expression. A parallel increase in AICD expression was not found. Patients showed increased expression of pho-TAU in the hippocampus. Findings were similar in patients with ALS and those with ALS-FTD, though more marked in the latter group. Conclusion: Post-mortem analyses showed that the amyloid cascade is activated in the hippocampus of patients with MND and correlated with cytoplasmic pho-TDP-43 expression. The number of intra- or extracellular aggregates of Aβ peptides was not significant.